The good companions based on the novel by J.B. Priestley - Priestley, J. B. 1894-1984; Johnson, Laurie 1927-2024 (Network, 2013)
J. Lee Thompson directs this 1950s musical comedy, based on the novel by J.B. Priestley, starring John Fraser, Rachel Roberts, Joyce Grenfell, Celia Johnson, Anthony Newley and Thora Hird. At the centre of the story is Susie Dean (Janette Scott), a talented young singer in variety troupe the Dinky Doos. Susie is concerned that her dreams of stardom are over when the Dinky Doos run into financial trouble, but with the aid of an unlikely trio, romantic former teacher Inigo Jollifant (Fraser), wealthy philanthropist Miss Trant (Johnson) and the practical Jess Oakroyd (Eric Portman), the troupe is reinvigorated and presented to a whole new audience
Original: Großbritannien, 1957
Keywords: Film; DVD-Video